The 'pears and lemons' protein UvPal1 regulates development and virulence of Ustilaginoidea virens. (23rd November 2020) - Chen, Xiaoyang; Tang, Jintian; Pei, Zhangxin; Liu, Hao; Huang, Junbin; Luo, Chaoxi; Tom, Hsiang; Zheng, Lu
Summary: Ustilaginoidea virens is an economically important fungus causing a devastating grain disease, rice false smut. An insertional mutagenesis screen was used to explore biological mechanisms underlying infection process of U . virens . T184, a new mutant was identified, with abnormal conidial morphology and deficient virulence. Analysis of the T‐DNA inserted gene UvPal1 in the mutant confirmed it as a putative homologue of a cellular morphogenetic protein in yeast, Pal1, whose function has not been well characterized. Deletion of UvPal1 affected hyphal growth, cell morphology, stress adaptation and virulence. UvPal1 could interact with the endocytic proteins, UvEde1 and UvSla2, but was not required for receptor‐mediated endocytosis. A yeast two‐hybrid (Y2H) analysis was further carried out to screen the UvPal1‐interacting proteins, resulting in the identification of 16 putative interacting proteins. Interestingly, UvPal1 interacted with a septin protein, UvCdc11 in vivo and in vitro, and also affected subcellular localization of UvCdc11 protein. Deletion of the four core septins impaired the growth, morphogenesis, stress response and virulence. Collectively, effects on cell morphology, oxidative stress response and virulence are similar to those of UvPal1, suggesting that UvPal1 physically interacts with UvCdc11 to mediate the septin complex to maintain the cellular morphology and virulence of U . virens .